Artificial intelligence the insights you need from Harvard Business Review - Wilson, H. James; McAfee, Andrew; Brynjolfsson, Erik; Davenport, Thomas H. 1954-; Ross, Jonathan Todd (Gildan Audio, 2019)
From making faster, better decisions to automating rote work to enabling robots to respond to emotions, AI and machine learning are already reshaping business and society. What should you and your company be doing today to ensure that you're poised for success and keeping up with your competitors in the age of AI' Artificial Intelligence: The Insights You Need from Harvard Business Review brings you today's most essential thinking on AI and explains how to launch the right initiatives at your company to capitalize on the opportunity of the machine intelligence revolution. Business is changing. Will you adapt or be left behind' Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues-blockchain, cybersecurity, AI, and more-each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow. You can't afford to ignore how these issues will transform the landscape of business and society. The Insights You Need series will help you grasp these critical ideas-and prepare you and your company for the future.
Downloadable audio file
Keywords: Computers; Electronic digital computers; Ordinateurs; computers; COMPUTERS; Intelligence (AI) & Semantics; Downloadable audio books; Audiobooks; Livres audio